FALLOW SYSTEM IMPROVEMENT (FSI) : TEKNIK AGROFORESTRI UNTUK MEMPERPENDEK WAKTU BERA DAN MENINGKATKAN KESUBURAN TANAH - Kaliman, Windrati (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2011)
Fallow System Improvement (FSI) is one of Agroforestry Technology that use for reducing periode time of fallow. The Obyective of the research is to improve soil fertility in the land fallow after sand mining using FSI by application gamal leaf as a mulch.Research method that was used is Experimental research with unit area of 10 m x 10 m plots for application of mulch. Soil analysis was done before and after mulch application in order to know the contain of nutrient of the soil.The study indicates that the land restoration through application mulch of Gliricidiasepium leaf( FSI) can improve organic material, P,K, and C content of the soil in the period time of 4 months.Therefore, the land can be planted 10 months after sand mining. It is less than the usual fallow is more than 2 years especially in the land after sand mining. Key Words: Fallow, Agroforestry Technology, Mulch, Gliricidia sepium